Expanding our Understanding of the Seaweed Holobiont: RNA Viruses of the Red Alga Delisea pulchra - Lachnit, Tim; Thomas, Torsten; Steinberg, Peter (Frontiers in Microbiology, 2016)
Marine seaweeds are holobionts comprised of the macroalgal hosts and their associated microbiota. While the composition of the bacterial component of seaweed microbiomes is increasingly studied, almost nothing is known about the presence, diversity and composition of viruses in macroalgae in situ. In this study, we characterise for the first time the viruses associated with a red macroalga, Delisea pulchra. Using transmission electron microscopy we identified diverse morphotypes of virus-like particles in D. pulchra ranging from icosahedral to bacilliform to coiled pleomorphic as well as bacteriophages. Virome sequencing revealed the presence of a diverse group of dsRNA viruses affiliated to the genus Totivirus, known to infect plant pathogenic fungi. We further identified a ssRNA virus belonging to the order Picornavirales with a close phylogenetic relationship to a pathogenic virus infecting marine diatoms. The results of this study shed light on a so far neglected part of the seaweed holobiont, and suggest that some of these may be possible pathogens for a host that is already known to be significantly impacted by bacterial infections.